Myelofibrosis-Associated Lymphoproliferative Disease: Retrospective Study of 16 Cases and Literature Review. (2nd November 2009) - Etienne, A.; Gruson, B.; Chatelain, D.; Garidi, R.; Royer, B.; Sevestre, H.; Marolleau, J. P.; Damaj, G.
Abstract : Background . To better describe the clinical, biological, and the outcome of non-Hodgkin's lymphoma (NHL) with, at the initial presentation, bone marrow fibrosis (MF). Patients and Methods . From January 2001 to January 2007, 16 eligible patients with NHL and MF were retrieved from the Pathology Department of the University hospital of Amiens. Median age of patients was 62 years (range 16–74) with a sex ratio male/female of 3. Results . MF is associated with all types of lymphoma predominantly with B-cell phenotype and it seems to be more associated with low-grade NHL. B-symptoms are more frequent at diagnosis and more patients presented with an elevated LDH level. JAK-2 was negative in the 10 patients analysed. Two patients presented with features of primary MF with no evidence of lymphoma. Overall response rate was 94% after the first line of therapy with regression or improvement of MF. Relapse occurred in 8 patients (47%) with recurrence of MF in all of them. After a median follow-up of 42 months, 12 patients were alive with an overall survival rate for the entire group of 75%. Conclusions . MF-associated NHL is a rare manifestation which may be associated with all types of NHL and its presence does not seem to confer a poor prognosis. A search for lymphoproliferation should be considered when the cause of MF is not apparent.